2004
DOI: 10.1189/jlb.0603291
|View full text |Cite
|
Sign up to set email alerts
|

Virally stimulated plasmacytoid dendritic cells produce chemokines and induce migration of T and NK cells

Abstract: The natural interferon (IFN)-producing cell is now known to be identical to the plasmacytoid dendritic cell (PDC). These are Lin-, CD123+, CD11c-, and human leukocyte antigen-DR+ cells that secrete large amounts of IFN-alpha (1-2 IU/cell) when stimulated by enveloped viruses such as herpes simplex virus. In the current study, we have evaluated chemokine expression by virally stimulated PDC. Up-regulation of mRNA for CCL4, CCL3, CCL5, CCL2, and CXC chemokine ligand (CXCL)10 in herpes simplex virus-stimulated PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 71 publications
7
142
0
2
Order By: Relevance
“…We also observed HSVinduced upregulation of MIP-1␤/CCL4 expression in macaque PDC (Fig. 8B and D), a finding similar to what we reported earlier for humans (28). Finally, similar to human PDC, macaque PDC expressed intracellular TNF-␣ in response to HSV stimulation (Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…We also observed HSVinduced upregulation of MIP-1␤/CCL4 expression in macaque PDC (Fig. 8B and D), a finding similar to what we reported earlier for humans (28). Finally, similar to human PDC, macaque PDC expressed intracellular TNF-␣ in response to HSV stimulation (Fig.…”
Section: Resultssupporting
confidence: 76%
“…IP-10 (CXCL10) and MIP-1␤ (CCL4) are inflammatory chemokines that chemoattract Th1-polarized T cells and NK cells, respectively. We have previous demonstrated that human PDC produce CXCL10 in response to either IFN-␣ or HSV, whereas HSV but not IFN-␣ induces the expression of CCL4 (28). In the macaque model, utilizing intracellular flow cytometry, we detected significant IP-10/CXCL10 production in HSV-stimulated PDC from 7 of 11 monkeys tested ( Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…As mentioned, the potential of PDCs to regulate leukocyte recruitment is mostly related to the ability of these cells to respond to viral infection with high levels of type I IFN production. HSV1-activated PDCs recruit T and NK cells through the production of CXCL9, CXCL10 and CCL4, and CD40-engagement further strengthens this response [78,79]. Exposure of PDCs to HIV-1 surface components triggers the secretion of the CCR5 ligands CCL3 and CCL4, suggesting a role of PDCs in limiting viral spreading [80].…”
Section: Modulation Of Leukocyte Recruitment By Pdcsmentioning
confidence: 93%
“…Initially, PDC were recognized for their role in innate antiviral immunity. However, it is now being revealed that these cells are involved in several aspects of immunity including directing cell trafficking via chemokine production (1,2), acting as accessory cells in B cell Ab production (3,4), and inducing Th1, Th2, or T reg responses, depending on the nature of the stimulation (5)(6)(7). Perhaps the best studied aspect of PDC function is their ability to produce the antiviral cytokine IFN-␣.…”
mentioning
confidence: 99%